Innovations in talent building : Kaivalya Education Foundation - Vohra, Neharika, 1966-; Pattnaik, Snigdha; Neelakantan, Niranjana ([London] : SAGE, 2016)
The study documents the practices, successes, failures, and lessons of the team at Kaivalya Education Foundation. It will reflect whether these innovations in building talent can be replicated by other organizations.
Originally Published in: Vohra, N., Pattnaik, S., & Neelakantan, N. (2014). Innovations in Talent Building: Kaivalya Education Foundation. OB0217. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Educational leadership -- Case studies; Social entrepreneurship -- Case studies